The Politics of LGBT Policy Adoption: Shibuya Ward’s Same Sex Partnership Certificates in the Japanese context - Takao, Yasuo (University of British Columbia, 2017)
This article will examine the determinants of LGBT (lesbian, gay, bisexual, and transgender) policy adoption in Shibuya, one of the twenty-three city wards of Tokyo, by taking an actor-specific approach to the first case of officially recognized same-sex partnership in Japan. How did the sexual minority issue become the subject of official agendas? How did actors both inside and outside the municipal government seize agenda-setting opportunities for government action? The results indicate that key policy makers’ entrepreneurship played a primary role in the official recognition of same-sex partnership by linking policy solutions with agenda-setting opportunities. This analysis demonstrates that the adoption of municipal LGBT policy does not necessarily reflect the redistribution of non-material resources, such as citizen values, but rather resembles the patterns of welfare politics.